2020
DOI: 10.1002/ange.202004125
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt Single‐Atom Catalysts with High Stability for Selective Dehydrogenation of Formic Acid

Abstract: Metal–organic framework (MOF)‐derived Co‐N‐C catalysts with isolated single cobalt atoms have been synthesized and compared with cobalt nanoparticles for formic acid dehydrogenation. The atomically dispersed Co‐N‐C catalyst achieves superior activity, better acid resistance, and improved long‐term stability compared with nanoparticles synthesized by a similar route. High‐angle annular dark‐field–scanning transmission electron microscopy, X‐ray photoelectron spectroscopy, electron paramagnetic resonance, and X‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 64 publications
0
10
0
Order By: Relevance
“…Obviously, the hydrogenation of CO 2 in basic aqueous solution is more feasible thermodynamically. However, in most cases of CO 2 hydrogenation, harsh conditions including high temperature, high pressure, and the use of organic solvents as well as catalyst are still required. , Although homogeneous catalysts based on Ru, Ir, Co, Fe, and so on , have been extensively investigated, reports of metal complexes under ambient conditions are still quite rare. For example, for Cp*Ir complexes (Scheme ), [Cp*Ir­(4-(1 H -pyrazol-1-yl-κN 2 )­benzoic acid-κC 3 )­(H 2 O)] 2 ­SO 4 reported by Fukuzumi and [Cp*Ir­(dhbp)­(H 2 O)]­SO 4 (dhbp = 4,4′-di­hydroxy-2,2′-bipyridine) reported by Fujita achieved respective 6.8 and 70 h –1 TOFs for CO 2 hydrogenation to produce formate under atmospheric pressure (CO 2 /H 2 = 0.05 MPa/0.05 MPa) at 25 °C.…”
Section: Introductionmentioning
confidence: 99%
“…Obviously, the hydrogenation of CO 2 in basic aqueous solution is more feasible thermodynamically. However, in most cases of CO 2 hydrogenation, harsh conditions including high temperature, high pressure, and the use of organic solvents as well as catalyst are still required. , Although homogeneous catalysts based on Ru, Ir, Co, Fe, and so on , have been extensively investigated, reports of metal complexes under ambient conditions are still quite rare. For example, for Cp*Ir complexes (Scheme ), [Cp*Ir­(4-(1 H -pyrazol-1-yl-κN 2 )­benzoic acid-κC 3 )­(H 2 O)] 2 ­SO 4 reported by Fukuzumi and [Cp*Ir­(dhbp)­(H 2 O)]­SO 4 (dhbp = 4,4′-di­hydroxy-2,2′-bipyridine) reported by Fujita achieved respective 6.8 and 70 h –1 TOFs for CO 2 hydrogenation to produce formate under atmospheric pressure (CO 2 /H 2 = 0.05 MPa/0.05 MPa) at 25 °C.…”
Section: Introductionmentioning
confidence: 99%
“…Highly active and efficient single-atom catalyst (SAC) system can be used for organic reaction. [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] We found that the driving force of the classical Co-mediated fluorination mechanism is mainly due to the generation of CoÀ F intermediates. [23,24,44] Therefore, we speculated that CoÀ F intermediates can be generated in situ through the oxidative fluorination of AgF using a stable low-valent Co SAC that drives the reaction smoothly.…”
Section: Resultsmentioning
confidence: 78%
“…The N 1s spectra (Figure 4b) revealed three types of N species, viz, pyridinic N, pyrrolic N, and graphitic N over Co-N x catalysts. 24,27 Through the comparison of the content of different N species from the respective characteristic peak (Table 2), we observed that the pyridinic N content increased from 24% to 50%, while the pyrrolic N content decreased from 60% to 30%, along with lowering of CN over Co-N x catalysts. This result suggested that the atomically dispersed Co coordinated mainly with the pyrrolic N. Collectively, these observations demonstrated that the geometric and electronic structures of the atomically dispersed Co catalyst were modulated through different CNs of the Co-N, which, in turn, influenced the catalytic activity during the NH 3 synthesis.…”
Section: Structure Characterizationmentioning
confidence: 94%
“…An apparent peak located at 1.5 Å for the as-synthesized Co-N x samples was attributed to Co-N coordination, compared with CoPc reference. 24 Meanwhile, no typical peaks for Co-Co coordination at 2.2 Å were visible, indicating the atomically dispersed Co atoms on these Co-N x catalysts. Besides, the peak intensity of Co-N coordination decreased with increased pyrolysis temperature, suggesting a decrease in Co-N CN.…”
Section: Structure Characterizationmentioning
confidence: 94%